(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: More than one third of teenage pregnancies was found in the Northeast of Thailand. The objective of this research was to examine the influence of personal, family, peer factors, sexuality attitude, and the comprehensive sexuality education (CSE) on teenage pregnancies in the Northeast of Thailand. Methodology: This case control study was conducted with the 1:3 proportion of case and control. The case were 60 teenage aged 15-19 years old, lived in the Northeast of Thailand, and delivered a baby less than 1 years. The control was 180 teenagers aged between 15 and 19 years old in the same region but never pregnant. Multiple logistic regression analysis was used to identify factors associated with teenage pregnancy presenting adjusted odds ratio and 95% confident Interval for the magnitude of association. P-value of <0.05 was statistically significant cut point. Result: Among 240 teenagers, 60 were teenage pregnancy with the mean age of 17.09±0.63 years old, whereas 180 teenagers were the control group with mean age of 16.83±0.56. The multiple logistic regression analysis indicated that had no to one brother (adj.OR=5.08; 95%CI: 2.28-11.35), had friend lived with her boyfriend (adj.OR=4.97; 95%CI: 2.33-10.58), had average level of sexual attitude (adj.OR=4.68; 95%CI: 2.82-10.79), had average level of CSE (adj.OR=4.56; 95%CI: 2.93-10.52) were associated with teenage pregnancy, when controlling other covariates. Conclusion: Family and peer factors, sexual attitude, as well as comprehensive sex education had influence on teenage pregnancy in the Northeast of Thailand. Effective comprehensive sex education is in need to help improve sexual attitude especially among those lived in the vulnerable family and peer environment. Families should closely supervise their children on sexuality, gender roles and social norms.